Sensitivity and Specificity Sputum Cytology Examination to Histopathology Examination of Lung Malignancy Suspect Patient in Dr. Mohammad Hoesin General Hospital Palembang - M. Afif Heldian Putra; Gama Satria; Dini Rizkie Wijayanti; Legiran; Bermansyah; Ahmat Umar; Aswin Nugraha (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Incidence of lung cancer highest in Indonesia and the fifth most abundant in female after breast cancer. Lung cancer is first cause of cancer related mortality in male (21.8%) and second cause of cancer related mortality in female (9.1%) after breast cancer (21.4%). The result of study in 100 hospitals in Jakarta showed that lung cancer was the most abundant in male and forth in female. The sputum cytology in lung cancer is an initial examination for diagnosis. The sputum cytology examination is a simple, accurate, cheap and non-invasive for initial diagnosis of lung disease including lung cancer. Methods: This study targeted lung malignancy suspect patient with sputum cytology examination in Dr. Mohammad Hoesin Hospital Palembang. The inclusion criteria were patients who will have a surgery and histopathology examination, patient >17 years old, patient that willingly take part in this research. The exclusion criteria were patient with sputum that can’t be retrieved. This study was using Cross Sectional method. The measurement of sensitivity and specificity of sputum cytology to histopathology examination calculated with Thornier-Remain formula. Results: The lung cancer patient found most in category of > 40 years (63.6%), male and smoking (77.3%). The sputum cytology’s result highest in non-malignancy (86.4%) and the histopathology examination’s result highest in malignancy (72.7%). Sensitivity of sputum cytology in this study is 28.75% and the specificity 100% Conclusion: The sensitivity of sputum cytology in 28.75% shown accuracy of sputum cytology method and specificity in 100% shown how often the sputum cytology method diagnoses the malignancy